Alpha-1 antitrypsin deficiency: outstanding questions and future directions - María Torres-Durán; José Luis Lopez-Campos; Miriam Barrecheguren; Marc Miravitlles; Beatriz Martinez-Delgado; Silvia Castillo; Amparo Escribano; Adolfo Baloira; María Mercedes Navarro-Garcia; Daniel Pellicer; Lucía Bañuls; María Magallón; et al. (Orphanet Journal of Rare Diseases, 2018)
Abstract Background Alpha-1 antitrypsin deficiency (AATD) is a rare hereditary condition that leads to decreased circulating alpha-1 antitrypsin (AAT) levels, significantly increasing the risk of serious lung and/or liver disease in children and adults, in which some aspects remain unresolved. Methods In this review, we summarise and update current knowledge on alpha-1 antitrypsin deficiency in order to identify and discuss areas of controversy and formulate questions that need further research. Results 1) AATD is a highly underdiagnosed condition. Over 120,000 European individuals are estimated to have severe AATD and more than 90% of them are underdiagnosed. Conclusions 2) Several clinical and etiological aspects of the disease are yet to be resolved. New strategies for early detection and biomarkers for patient outcome prediction are needed to reduce morbidity and mortality in these patients; 3) Augmentation therapy is the only specific approved therapy that has shown clinical efficacy in delaying the progression of emphysema. Regrettably, some countries reject registration and reimbursement for this treatment because of the lack of larger randomised, placebo-controlled trials. 4) Alternative strategies are currently being investigated, including the use of gene therapy or induced pluripotent stem cells, and non-augmentation strategies to prevent AAT polymerisation inside hepatocytes.